Strategi Pendidikan Islam Dalam Pengembangan Kecerdasan Spritual Anak Usia Dini Di TK Prima Sakinaah Islamic School Kota Bekasi - Irma Irma (Ash-Shobiy: Jurnal Pendidikan Islam Anak Usia Dini dan Al-Qur'an, 2026)
The results of the study show that the development of spiritual intelligence in early childhood at Prima Sakinah Islamic School occurs through three main strategies, namely religious habits, integration of Islamic values in learning activities, and consistent role modeling by teachers. These three strategies complement each other and effectively stimulate spiritual aspects because they are in line with the learning characteristics of early childhood, which rely on direct experience, repetition, and imitation. These findings confirm that the formation of spiritual intelligence is not only supported by teaching materials, but also by the environment, interactions, and Islamic school culture.Based on these findings, Islamic PAUD institutions are advised to design more systematic and documented spiritual development strategies to facilitate evaluation and program continuity. Further research can expand observations to other Islamic PAUD institutions or use a field approach to provide a more in-depth picture of the implementation of Islamic education strategies in strengthening children's spiritual intelligence.